The Difference of Physics Learning Result Between Cooperative Learning Model Type Predict, Observe, Explain With The Conventional Learning at The Students Class X MAN 3 Padang - Noftiana, Noftiana (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The learning model is used to help the students in understanding the abstracted learning materials and make the teacher easy when doing the teaching-learning process activity. This research is aimed to know the difference of the Physics learning result between cooperative learning model type Predict, Observe, Explain (POE) with the conventional learning at the students class X MAN 3 Padang. The formulated hypothesis is that there is a significant difference at the Physics learning result between cooperative learning model type Predict, Observe, Explain (POE) with the conventional learning at the students class X MAN 3 Padang. The research which is used is quasy experiment with the research design is randomized control group only design. Population of this research is all the students of class X MAN 3 Padang that number 118 studentswith sample is class X2 as experiment class and class X1 as control class. The tabulation of final test data is done through the hypothesis test which uses t-test, because the data distributed normally and homogeny. It is chosen three of Physic education experts who participate in validating process. The highest validation score at cognitive aspect by using the POE method is 75, 25. Whereas at affective aspect is 84, 51 and at physic motorist aspect is 77, 00. It is from the three of validators recommend that the POE method is appropriate forbeing used as one of models in learning Physics at MAN.